PSYCHOLOGICAL ASPECTS OF OPHTHALMOLOGIC EXAMINATION IN CHILDREN AGED 0–6 YEARS: A LITERATURE REVIEW (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Early childhood (0–6 years) represents a critical period for visual system development. Timely ophthalmologic examination enables early detection of refractive errors, amblyopia, strabismus, congenital anomalies, and other ocular pathologies. However, diagnostic accuracy in this age group depends not only on clinical techniques but also on psychological and behavioral factors.